The " youtubification " of politicized rhetoric an ideological analysis of Juana change youtube videos - Ancheta, Jan Girard R. (2011)
Juana Change is one of the most prominent Filipino cyberactivists who's been advocating her causes throughout the internet. She is known for tackling issues about the country's problems by uploading political satires in the video-sharing website, YouTube.com. This study is an ideological analysis of Juana Change's discourse that aims to derive the dominant ideologies embedded in each video. The researcher employed Aristotle's Five Cannons of Rhetoric and his Three Modes of Appeals to analyze the rhetorical strategies and devices that Juana Change puts forth in her arguments. Stuart Hall's Encoding/ Decoding Model was also used to examine the reception of Juana Change's viewers as a persuasive speech artifact. The researcher derives three ideologies manifested from Juana Change's political satires: good governance, unity and vigilance. A possible political implication of these ideologies holds influence to the viewers on choosing competent leaders during the 2010 elections. Juana Change's discourse is also socially significant in changing the attitudes of its viewers by rousing them from a previously apathetic stance regarding the country's alarming political scenario -- Author's abstract.